2010
DOI: 10.1177/194008291000300203
|View full text |Cite
|
Sign up to set email alerts
|

Asian Elephant Elephas Maximus Habitat Use and Ranging in Fragmented Rainforest and Plantations in the Anamalai Hills, India

Abstract: The persistence of wide-ranging mammals such as Asian elephants in fragmented landscapes requires extending conservation efforts into human-dominated landscapes around protected areas. Understanding how elephants use such landscapes may help facilitate their movements and reduce conflict incidence. We studied elephants' use of fragmented habitats and ranging patterns of focal herds in a landscape of rainforest fragments embedded in tea, coffee, and Eucalyptus plantations in the Anamalai Hills. Elephant herds e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
72
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(75 citation statements)
references
References 32 publications
3
72
0
Order By: Relevance
“…This has been validated by the work of Kumar et al (2010), who showed that the high concentration of locations of two herds in Sholayar River and its tributaries in South India during the dry season reflects the influence of water and food availability on spatial distribution. Sukumar (1989) also emphasized that small home ranges are associated with rich and diverse habitats.…”
Section: Forummentioning
confidence: 69%
“…This has been validated by the work of Kumar et al (2010), who showed that the high concentration of locations of two herds in Sholayar River and its tributaries in South India during the dry season reflects the influence of water and food availability on spatial distribution. Sukumar (1989) also emphasized that small home ranges are associated with rich and diverse habitats.…”
Section: Forummentioning
confidence: 69%
“…Over the past 40 years, this natural habitat has been reduced by at least 60% following forest conversion to other types of land use (primarily agriculture) (Gaveau et al ., ). Elephants increasingly rely on non‐protected areas for their movements and dispersal, and food ranging activities (Fernando et al ., ; Kumar et al ., ; Gaveau et al ., ). Several Managed Elephant Ranges are completely isolated from other elephant populations in extensive oil‐palm production landscapes; for example, Tabin Wildlife Reserve and Lower Kinabatangan.…”
Section: Reasons For Increasing Human–elephant Conflicts In Sabahmentioning
confidence: 96%
“…Since wildlife corridors are typically narrow and vulnerable, they must be managed with extreme caution. However, many wildlife corridors are getting encroached upon by people (Kushwaha and Hazarika 2004;DeFries et al 2005;Giriraj et al 2008;Kumar et al 2010). To minimize these, a structural and functional connectivity between the PAs are crucial.…”
Section: Resultsmentioning
confidence: 97%
“…In the countries like India, with growing economy and boom to urbanization, human beings are moving towards forests (Nepali 2006), clearing vast amount of flora and fauna (Srivastava et al 2002). This has resulted in habitat fragmentation (Kumar et al 2010), range reduction (Kushwaha and Hazarika 2004;Giriraj et al 2008), shrinking corridors between PAs (DeFries et al 2005), increasing human-wildlife conflicts (Choudhury 2004;Blaustein 2007) and local species extinctions (Pimm and Raven 2000).…”
Section: Introductionmentioning
confidence: 97%